Effects of levelling of the curve of Spee on the proclination of mandibular incisors and expansion of dental arches: a prospective clinical trial - Pandis Nikolaos; Polychronopoulou Argy; Sifakakis Iosif; Makou Margarita; Eliades Theodore (Sciendo, 2023)
To investigate the effects of levelling the curve of Spee (COS) on the inclination of the mandibular incisors and the width of the mandibular arch.